2006
DOI: 10.1002/cncr.2820450110
|View full text |Cite
|
Sign up to set email alerts
|

Breast thermography and cancer risk prediction

Abstract: Thermography makes a significant contribution to the evaluation of patients suspected of having breast cancer. The obviously abnormal thermogram carries with it a high risk of cancer. This report summarizes the results of patients with questionable or stage Th 111 thermograms. From approximately 58,000 patients, most of whom had breast complaints, examined between August 1965 and June 1977, the conditions of a group of 1,245 women were diagnosed at initial examination as either normal or benign disease by conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 3 publications
1
35
0
5
Order By: Relevance
“…In one of the earliest studies carried out by Gautherie and Gros in 1980 [13], patients with a thermogram stage 4 or 5 had a 90% chance of being affected by cancer at the time of study, while 38% of the TH3 cases (suspicious but not conclusive) developed cancer within 1-4 years of follow-up. Similarly, in a recent review by Lahiri et al [14], an abnormal pattern in infrared images could identify a high risk for breast cancer development in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the earliest studies carried out by Gautherie and Gros in 1980 [13], patients with a thermogram stage 4 or 5 had a 90% chance of being affected by cancer at the time of study, while 38% of the TH3 cases (suspicious but not conclusive) developed cancer within 1-4 years of follow-up. Similarly, in a recent review by Lahiri et al [14], an abnormal pattern in infrared images could identify a high risk for breast cancer development in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has probably been most investigated for breast cancer [6][7][8][9][10][11][12][13], but growing literature reports its use in a variety of other medical conditions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, however, there are only two reports of the use of DITI in skeletal trauma.…”
Section: Introductionmentioning
confidence: 96%
“…These might not be observed in other modalities which depend upon detecting architectural distortions that appear only when tumor is sufficiently grown. A study by Gautherie and Gros [3] over 58,000 patients for 12 years showed that thermography detected breast cancer five years earlier in around 400 patients than mammography and ultrasonography.…”
Section: Biological Explanationmentioning
confidence: 99%